Exploring the role of content and language integrated learning approach in developing transversal skills in university students with respect to the mediating role of emotional intelligence - Jiang, Peijun; Akhter, Shamim; Azizi, Zeinab; Gheisari, Asma; Kumar, Tribhuwan (Frontiers in Psychology, 2022)
Although a range of studies has explored the effects of the content and language integrated learning (CLIL) approach on students’ achievement, its impact on improving university students’ transversal skills (TSs) has remained largely unexplored in Iran. Thus, the present study has a two-fold purpose. First, it aims to investigate the role of the CLIL approach in improving Iranian university students’ TSs. Second, it purports to explore the mediating role of emotional intelligence (EI) in the relationship between the CLIL approach and TSs. For this purpose, a survey design was used wherein a research-made questionnaire was distributed among 123 university students to gather the required data. Findings disclosed that the CLIL approach had a positive role in developing the university students’ TSs. Further, the results indicated that EI positively affected the development of TSs in university students. Moreover, the findings evidenced that EI significantly mediated the relationship between the CLIL approach and the development of the university students’ TSs. The study concludes that applying the CLIL approach involves an entirely new paradigm, offering valuable implications for relevant stakeholders.